Hak Asasi Manusia dalam Pendidikan - Bachrudin Musthafa (Universitas Negeri Malang, 2016)
In our everyday discourse many good things have been done and attributed for the sake of wellbeing of children. This paper questions the effectiveness of what we have been doing in education in the name of children by, first, portraying children and adolescents according to recent scholarship, and then presenting problems in our current educational practice. To address the problems which arise from the observation, some strategic steps are then presented to conclude the discussion